Leveraging AI-Driven Predictive Analytics in Modern ERP Systems - Ravi Sankar Korapati, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of AI-driven predictive analytics in modern Enterprise Resource Planning (ERP) systems. The article examines how the integration of artificial intelligence and machine learning capabilities has revolutionized organizational decision-making processes, operational efficiency, and strategic planning. The article investigates key application areas including financial forecasting, inventory optimization, and customer behavior analysis, while also addressing technical implementation considerations and system architecture requirements. The article demonstrates how AI-enhanced ERP systems have enabled organizations to achieve significant improvements in operational performance, risk management, and market competitiveness through advanced data processing and predictive modeling capabilities.
Keywords: Artificial Intelligence; Enterprise Resource Planning; Machine Learning; Predictive Analytics; Real-time Integration